2020
DOI: 10.2147/jep.s275791
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of Inflammation on the Healing Process of Acute Skin Wounds Under the Treatment of Wounds with Injections in Rats</p>

Abstract: Purpose To study the effects of inflammation on the healing process of rats’ acute skin wounds during treatment with different injections. Methods The study was carried out on Wistar rats, on which square wounds were simulated in the back region. Four groups of wounds were studied. On the day of the simulation (day 0), solutions of the drugs were injected into the wounds: an isotonic sodium chloride solution (Control group), mesenchymal stem cells (SC group), collagen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
13
0
3
Order By: Relevance
“…The composition and technology of the drugs PCCD, MSC, and PCCD + MSC have been published previously [30][31][32][33][34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition and technology of the drugs PCCD, MSC, and PCCD + MSC have been published previously [30][31][32][33][34].…”
Section: Methodsmentioning
confidence: 99%
“…However, not enough research has yet been done investigating this new direction to provide data that meet all the requirements of evidence-based medicine. In our previous research, we developed new dressing biomaterials for the treatment of wounds containing polymers, mesenchymal stem cells, and nanoparticles of cerium dioxide (CeO2), and demonstrated their preliminary safety and efficacy [30][31][32][33][34]. We have chosen CeO2 nanoparticles as the metal included in our biomaterials because previous studies have shown that it has low toxicity and high biocompatibility, as well as the ability, depending on the changing pH of the wound, to provide electron transfer through the transition from Ce3+ to Ce4+ valence and vice versa [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory process of the skin is characterized by pain, redness, swelling, heat, and loss of function [ 12 , 52 ]. In a wound-healing process, inflammation is very important for the detection and elimination of pathogenic microorganisms, removal of damaged tissue, and cleaning of the affected area [ 53 ]. The skin can suffer various types of inflammatory processes that can be caused by a series of chemical or mechanical harmful agents, pathogens, or an autoimmune or allergic response [ 10 , 52 ].…”
Section: Inflammatory Process Of the Skinmentioning
confidence: 99%
“…Interactions between skin cells, such as fibroblasts and keratinocytes, occur and impair the tissue remodeling process. Thus, chronic wounds are marked by high levels of inflammation, decreased production of growth factors and proliferation of endothelial cells, and by non-re- epithelialization [ 48 , 52 , 53 ]. It is believed that ROS are also involved in chronic inflammatory responses, after an overload of the skin’s antioxidant capacity.…”
Section: Inflammatory Process Of the Skinmentioning
confidence: 99%
“…Although many animal studies used MSCs as a treatment to heal skin wounds [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], currently, no systematic reviews or meta-analyses have demonstrated high-quality efficacy of MSC treatment. In addition, no widely accepted method exists for introducing MSCs into an animal organism.…”
Section: Introductionmentioning
confidence: 99%